2011
DOI: 10.1128/jcm.01993-10
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Putative Virulence Genes in Streptococcus mutans Strains Does Not Correlate with Caries Experience

Abstract: Streptococcus mutans, a member of the human oral flora, is a widely recognized etiological agent of dental caries. The cariogenic potential of S. mutans is related to its ability to metabolize a wide variety of sugars, form a robust biofilm, produce copious amounts of lactic acid, and thrive in the acid environment that it generates. The remarkable genetic variability present within the species is reflected at the phenotypic level, notably in the differences in the cariogenic potential between strains. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
2
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 88 publications
4
42
2
3
Order By: Relevance
“…There have been several attempts to correlate carriage of certain genotypes of S. mutans with caries incidence, however there has been no consensus among multiple studies [18][23]. Additionally, it has been reported that there was no correlation between the caries status of an individual and the distribution of 41 putative virulence genes or genetic elements in 33 S. mutans isolates [24]. These authors [24] concluded that the virulence genes they tested might be part of the core genome of S. mutans , hence the lack of diversity in their distribution among strains.…”
Section: Introductionmentioning
confidence: 99%
“…There have been several attempts to correlate carriage of certain genotypes of S. mutans with caries incidence, however there has been no consensus among multiple studies [18][23]. Additionally, it has been reported that there was no correlation between the caries status of an individual and the distribution of 41 putative virulence genes or genetic elements in 33 S. mutans isolates [24]. These authors [24] concluded that the virulence genes they tested might be part of the core genome of S. mutans , hence the lack of diversity in their distribution among strains.…”
Section: Introductionmentioning
confidence: 99%
“…Strains were streaked onto solid Todd-Hewitt medium and grown anaerobically for three days. Cell lysis and chromosomal-DNA isolation were performed as previously described [20], [21].…”
Section: Methodsmentioning
confidence: 99%
“…ISSmu5, formerly IS1216, comprised 15-bp terminal IRs flanked with 10-bp DR sequences (GenBank accession no. AF104381) and was a rarely found IS in 2 of 33 isolates (6.1%) of S. mutans; the copy number was determined as 10 and 2 in each isolate by hybridization analysis (Argimón and Caufield, 2011). It has been demonstrated that ISSa4 is found in 21 of 113 strains (18.6%) of human origin and the presence of ISSa4 is limited in strains of serotypes II and II/c (Dmitriev et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Utilizing their resistance to bacitracin, clinical isolations of both organisms are carried out on a selective mitis-salivarius bacitracin (MSB) medium (Loesche, 1986). In S. mutans, five insertion sequences, ISSmu1, ISSmu2, ISSmu3, ISSmu5, and IS199, have been identified (Argimón and Caufield, 2011).…”
Section: Introductionmentioning
confidence: 99%